Construcción de una Incubadora Artificial de Huevos (2022)
This document shows the construction of an artificial incubator, to improve the conditions of supply of chicks to the peasants of the Aurora area, Chiriguana corregimiento in the department of Cesar, this proposal was elaborated from a bibliographic review, then with Based on the results obtained, the particular requirements for this project were defined, after analyzing the information, the best option was selected, taking into account the use of low-cost materials, with the manufactured incubator, validation tests are carried out to verify the operation and the results, finally culminating in the preparation of the use and maintenance manuals, it can be seen in the validation results that the percentage of success in incubation is high, close to 90% hatching of the incubated eggs, so At a general level, the peasant community of the area is being favored, with this it is intended to improve the competitiveness of the area in the sheds dedicated to raising chickens.